MXene-coated multi-response conductive film based on layer-by-layer assembly strategy for electromagnetic interference shielding - Yanting Wang (Elsevier, 2021)
With the rapid development of wearable electronic products and smart devices, there is an urgent need to develop efficient electromagnetic interference (EMI)shielding materials to eliminate the resulting radiation pollution. Herein, hydrophobic and multi-responsive conductive composite film with core-shell structure and sandwich structure are constructed via simple in-situ polymerization and dip coating methods. The thin silicone coating can enhance the bonding fastness of the substrate and the conductive functional layer and endow the composite film excellent waterproof performance. The composite film with a thickness of 45 μm exhibits outstanding electrical conductivity of 62.15 S/cm and EMI shielding effectiveness (EMI SE) of 37.71 dB. Surprisingly, the composite film also exhibits good waterproof performance and excellent electro-optical thermal response, and has good stability in complex environments. This work proves the advantages of constructing multiple conductive interfaces inside the nanofiber film, and provides a new preparation strategy for efficient multifunctional shielding materials, which is expected to be widely used in the next generation of wearable electronic devices and wearable smart clothing.